(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Organisational culture is a facet that impacts every organisation’s functioning, different organisation needs different quite culture to be set up. it’s defined in terms of shared meaning, patterns of beliefs, rituals, symbols, and myths that evolve over time, service to scale back human variability and control and shape employee behavior in organisation. this research aims to compare private sector and public sector banks in terms of values of employees. The study attempts to understand the impact of OCTAPACE model on banking employees of private and public sector banks in Andrapradesh.The main implication of this research on organisational culture suggest that there is a scope for further improvement in the sample study organisations which would improve their work life by overcoming the monotony.